British Signals Intelligence on Argentine Naval Communications during the Falklands War: Collection, Processing and External Collaboration (Journal of the Spanish Institute for Strategic Studies, 2025)
Although the interception of Argentine naval communications by British intelligence during the Falklands War played a decisive role in the conflict, numerous issues, such as the extent of the interceptions, their actual relevance to the outcome, and almost everything regarding how these interceptions occurred, remain unresolved to this day. The aim of this article is to advance the understanding of these issues in the absence of the declassification of official documents on the subject. To this end, it analyzes the most likely intelligence-gathering methods, the intelligence activity prior to the Argentine landing operation, and seeks to contextualize this with the most recent information regarding intelligence cooperation between the Americans and the British in past decades, as it seems to offer a strong explanatory framework for understanding how the services involved operated. In this way, the article aims to provide criteria to more accurately evaluate or reevaluate the factors that determined the outcome and shaped the course of the war.
Keywords: SIGINT, Falklands, GCHQ, NSA, signals intelligence, satellite